2019
DOI: 10.1186/s13023-019-1199-x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the fiscal impact of rare diseases using a public economic framework: a case study applied to hereditary transthyretin-mediated (hATTR) amyloidosis

Abstract: Background: A wide range of rare diseases can have fiscal impacts on government finances that extend beyond expected healthcare costs. Conditions preventing people from achieving national lifetime work averages will influence lifetime taxes paid and increase the likelihood of dependence on public income support. Consequently, interventions that influence projected lifetime work activity, morbidity and mortality can have positive and negative fiscal consequences for government. The aim of this study was to appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Third, this study examines only direct healthcare costs and does not include indirect costs such as reduced work productivity. Moreover, while we did not examine the effect of demographic factors, such as age, on the burden of illness, we would expect to find greater burden in certain populations similar to what has been found in other amyloidosis studies [14,28]. Additionally, costs prior to diagnosis, which may also contribute to burden, were not captured.…”
Section: Limitationsmentioning
confidence: 78%
See 2 more Smart Citations
“…Third, this study examines only direct healthcare costs and does not include indirect costs such as reduced work productivity. Moreover, while we did not examine the effect of demographic factors, such as age, on the burden of illness, we would expect to find greater burden in certain populations similar to what has been found in other amyloidosis studies [14,28]. Additionally, costs prior to diagnosis, which may also contribute to burden, were not captured.…”
Section: Limitationsmentioning
confidence: 78%
“…Additionally, the study reported the greatest disease burden for this group [28]. A fiscal cost model found that patients with ATTRv amyloidosis in the Netherlands pay less taxes and receive incrementally more in government intervention, with the conclusion that halting disease progression early would result in economic benefits beyond health benefits [14]. In the simulated disease scenarios, patients with severe cardiomyopathy had less significant health costs due to early mortality compared to patients without severe cardiomyopathy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some had to adapt their schedule because they were unable to handle work-related stress or the fatigue related to the disease. Diseases that impact daily life, especially those that manifest at early ages, can lower lifetime earnings, savings and wealth accumulation, which can influence living standards in all life stages [ 24 ]. The disease was reported to lower the incomes of 29.8% of those surveyed, with its impact on patient income more important for those older than 50 years of age and in advanced stages of the disease, independently of the time since diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some had to adapt their schedule because they were unable to handle work-related stress or the fatigue related to the disease. Diseases that impact daily life, especially those that manifest at early ages, can lower lifetime earnings, savings and wealth accumulation, which can in uence living standards in all life stages (24). The disease was reported to lower the incomes of 29.8% of those surveyed, with its impact on patient income more important for those older than 50 years of age and in advanced stages of the disease, independently of the time since diagnosis.…”
Section: Discussionmentioning
confidence: 99%